2019
DOI: 10.5964/jspp.v7i1.1065
|View full text |Cite
|
Sign up to set email alerts
|

The perceived impact of the 2016 election: A mediation model predicting health outcomes

Abstract: The present study examined the relationship between the self-reported personal impact of the election of President Donald J. Trump, as measured by the Personal Impact of the Election Scale (PIES), and physical and mental health. A sample of 299 MTurk Amazon workers completed an online survey, including measures of the perceived personal impact of the 2016 presidential election, thought suppression, and mental and physical health. A mediation model was tested, with thought suppression included as a mediator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Few studies have examined the potential impact of politics on employee outcomes. For example, in a study of adult participants recruited from Mturk, Koerten et al (2019) reported that the perceived personal impact of the 2016 Presidential election results was negatively associated with both the mental and physical health, and that this relationship was partially mediated by thought suppression. Another article, by Beck and Shen (2019), also examined the effects of the 2016 Presidential election results on worker engagement and found that Democrats (who lost the election) experienced lower levels of engagement immediately following the election while Republicans (who won the election) did not.…”
Section: Current Research On Political Affiliations and Organizationsmentioning
confidence: 99%
“…Few studies have examined the potential impact of politics on employee outcomes. For example, in a study of adult participants recruited from Mturk, Koerten et al (2019) reported that the perceived personal impact of the 2016 Presidential election results was negatively associated with both the mental and physical health, and that this relationship was partially mediated by thought suppression. Another article, by Beck and Shen (2019), also examined the effects of the 2016 Presidential election results on worker engagement and found that Democrats (who lost the election) experienced lower levels of engagement immediately following the election while Republicans (who won the election) did not.…”
Section: Current Research On Political Affiliations and Organizationsmentioning
confidence: 99%
“…An increase in emotional reactivity may be particularly apparent in the days directly following an election (Neupert et al, 2021 ). Furthermore, those who report higher levels of perceived negative impact based on an election are more likely to report lower levels of physical and mental health (Koerten et al, 2019 ). Understanding the interconnectedness of democratic engagement and daily stressor exposure is imperative when considering elections in relation to well-being and how these stress processes may unfold within a person over time.…”
Section: Introductionmentioning
confidence: 99%